2018
DOI: 10.1212/01.wnl.0000542492.00605.9d
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of hospital admission for mood disorders following admission for epilepsy

Abstract: Admission for epilepsy was independently associated with subsequent hospital readmission for mood disorders. The magnitude of elevated risk in this population suggests that patients admitted with epilepsy may warrant targeted psychiatric screening during their hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Medical comorbidities such as hypertension, diabetes, renal disease, coagulopathies, autoimmune disease, sepsis, and psychiatric disorders were identified using validated ICD‐9‐CM codes 13 from previously published studies and/or Clinical Classification Software codes, which consist of grouped ICD‐9‐CM codes developed as a publicly available software tool via HCUP 24–29 . Codes for nausea and vomiting and rheumatoid arthritis were obtained from manual review of ICD‐9 codes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical comorbidities such as hypertension, diabetes, renal disease, coagulopathies, autoimmune disease, sepsis, and psychiatric disorders were identified using validated ICD‐9‐CM codes 13 from previously published studies and/or Clinical Classification Software codes, which consist of grouped ICD‐9‐CM codes developed as a publicly available software tool via HCUP 24–29 . Codes for nausea and vomiting and rheumatoid arthritis were obtained from manual review of ICD‐9 codes.…”
Section: Methodsmentioning
confidence: 99%
“…grouped ICD-9-CM codes developed as a publicly available software tool via HCUP. [24][25][26][27][28][29] Codes for nausea and vomiting and rheumatoid arthritis were obtained from manual review of ICD-9 codes. Additional covariates such as age and income quartile were obtained from the NRD.…”
Section: Key Pointsmentioning
confidence: 99%
“…Dr Mackenzie C. Cervenka started the symposium by addressing hospital admissions of patients with intellectual developmental disabilities (IDD) to the Epilepsy Monitoring Unit (EMU). 22 The unique challenges of individuals admitted to the unit, as well as their caregivers and treating team were discussed. The patient Adam offered key takeaways that brought the message home from the lens of a patient.…”
Section: Best Practices In Clinical Epilepsy Symposiummentioning
confidence: 99%
“…In the general population, the average unplanned (or acute) readmission rate within 30 days of epilepsy- or seizure-related hospitalisations is 10%, with epilepsy or seizure being the most common indication [ 20 , 21 ]. Other common reasons for readmission within a year include psychiatric disorders [ 22 , 23 ] and suicide attempts [ 24 ]. Few studies have reported readmission after epilepsy hospitalisation in people with intellectual disability, with one observing an increased risk of readmission in children with intellectual disability compared to children without [ 20 ].…”
Section: Introductionmentioning
confidence: 99%